CITRA PEREMPUAN DALAM NOVEL “PEREMPUAN DI TITIK NOL” KARYA NAWAL EL-SAADAWI - Ga Djami, Desy Oktaviana; A.Nai, Firmina; Djokaho, Margareta P.E. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2023)
This research written by Desy Oktaviana Ga Djami with the title “The image of women in the novel women at point zero by Nawal El-Saadawi”. Supervisor by Dr. Firmina A, Nai. M.Si and Margaretha Djokaho, S, Sn. M.Pd. this research focuses on the image of the main famale character in the novel Women at Point Zero by Nawal El- Saadawi. The novel Women at Point Zero by Nawal El-Saadawi is the object of research as material for analysis to find the image of women. This research uses theory according to the view of feminism from Sugihastuti (2000) as a reference to find the image of women consisting of women’s self-image and women’s social image. The method used is descriptive qualitative with the type of data descriptive qualitative. The data collection technique used is reading the novel carefully and thoroughly, underlining words, senteces and events that are the core of the analysis to find image of women that refers to feminism, and citing the results of data analysis by entering all the data into coding card. The results of the research found from the image of women in the novel women at point zero are that the physical image of women consisting of fivee units analysis, the psychological image of women thirteen units of analysis, the social image of the family six units of analysis, and the social image of society five units of analysis.